ONLINE RETAIL FOOD SHOPPING DURING THE COVID-19 PANDEMIC PERIOD - Ahmet Buğra Hamşıoğlu; Serhat Karaoğlan (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
This study was conducted to measure consumer attitudes towards online retail food shopping and the impact of the Covid-19 pandemic on these attitudes. Therefore, data were collected from 390 volunteers through an online survey in the first half of 2021, when the pandemic was intense. Effects of perceived convenience, risk, price advantage and trust factors on purchase intention were studied. For this, a structural equation model was performed. Then, the moderator effect of pandemic anxiety was examined. Finally, consumers were grouped according to the number and amount of online shopping. The differences between the means of the groups regarding the factors in the model were examined. According to the results, perceived convenience, price advantage, and trust factors have positive and significant on purchase intention; perceived risk factor has a negative and significant effect. It has been found that pandemic anxiety moderates the relationship between risk and price with purchase intention. It is seen that the light online shoppers differ from the moderate and heavy online shoppers in the convenience, risk and trust perception, and purchase intention. Moderate and heavy online shoppers differ only in the trust factor. There was no statistically significant difference between the three groups regarding perceived price advantage and pandemic anxiety.